Caribbean Collections in European Museums and the Question of Returns. Issue 4 (14th December 2017) - Françozo, Mariana; Strecker, Amy
Abstract: Since 2014, when the Caribbean Community officially launched its claim against former European colonial powers for reparations for slavery and native genocide, there has been a renewed interest in the question of cultural reparations and, more specifically, Caribbean cultural objects located in European museums. Yet information about such material remains scarce; there have been no formal claims for returns, and the legal status of Caribbean collections in European museums is anything but clear. This article aims to address these issues. First, we sketch the profile of Caribbean archaeological collections located in European museums to shed light on their nature and provenance. On this basis, we then move on to analyzing the legal status of such collections in light of international law, before discussing the broader political and ethical framework of returns and the role of cultural cooperation in reparatory justice for the Caribbean more generally.